Analisis Permintaan Tas Anak di UD Wijaya Menggunakan Metode Peramalan Time Series - Adi Lesmana, Nurma Yogi; Widyaningrum, Dzakiyah; Negoro, Yanuar Pandu (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
At this time, the Industry is more diverse and developing rapidly. Industrial development causes many companies to think of ways to survive and face fierce competition, which becomes a challenge for companies, especially for small MSME industries in their development stage. The establishment of this strategy is necessary to deal with changing market conditions as well as customers. Fulfillment of past demand is related to products (quantity and quality) and also raw materials and the increase in demand for a product varies. Consumer demand is uncertain, so methods that can minimize uncertainty are needed, one of which is the forecasting method. Forecasting uses historical data on sales demand and product usage so that it can be produced in the right quantity as well. UD Wijaya is one of the bag manufacturers. Produce bags continuously in constant quantities. This if not managed properly, will cause overstock and understock Therefore, this study uses forecasting methods to forecast the next 3 months, this study compares 4-time series forecasting methods Moving Average, Weighted Moving Average, Single Exponential Smoothing and Double Exponential Smoothing. The four methods compared the smallest MAD, MAPE, MSE, and MAPE values and the results in the next 3 months with a moving average of 3 as much as 240 pcs, 280 pcs, 280 pcs